Fuel combustion synthesis and upconversion properties of Yb3+ and Er3+ dual-doped ZrO2 nanocrystals - Liu, Xiao-lin; Zhang, Ning; Li, Dan; Li, Zhi-cheng; You, Wei-xiong; Zhang, Qian; Xia, Li-bin; Yang, Bin (Journal of Central South University, 2017)
Ytterbia and erbia dual-doped zirconia (ZrO 2 : Yb 3+ , Er 3+ ) nanophosphors were successfully synthesized by high-temperature fuel combustion at 1000 °C for 2 h. The effects of dopant concentration on the structure and upconversion properties were investigated by X-ray diffraction, transmission electron microscopy and photoluminescence, respectively. XRD patterns indicate that the main phase of products belongs to cubic ZrO 2 fluorite-type structure. TEM results show that different fuels have great influence on the morphologies of dual-doped ZrO 2 samples. Under 980 nm excitation, the glycine-calcined nanophosphors show high stimulated luminescence and doped-ion concentration-depended intensities. The intensely red upconversion emissions are attributed to the fact that the dual-doped Yb 3+ and Er 3+ ions result in the non-radiative relaxation, energy migration, and cross relaxation.